Análise da problemática do lixo nas romarias em Juazeiro do Norte - Ce - Pereira, Cieusa Maria Calou e (2005)
The present work analyzes, in Juazeiro do Norte – Ceará, waste sdid problematic during the pilgrimages’ days, with enphasis in: social, economical and environmental conditions. This city has a population of 214 thousand inhabitants, which is duplicated during the three religious parties at pilgrimages period. It causes an overload in public services, especially in appropriate waste solid management. The methodology dialectic was used in this research. Initially, this methodology made possible to do diagnosis of waste solid current situation. Moreover, the present research characterized and quantified the waste solid in the days of pilgrimages, identified the negative impacts of those residues and verified who are the produtors. As well as, it analyzed role and responsibility of environmental subject at Municipality of Juazeiro do Norte - Ceará. The deposits of recyclable materials were lifted up to verify the demand and to analyze the situation’s collectors of those materials. The Juazeiro do Norte’s landfill were identified through field research during the period of the municipal administrations between 1980 and 2005. The social actors and their respective educational actions in the city were considered to searching the problem’s solution. The studied subjects were analyzed with base in those elements to enhance that the city of Juazeiro do Norte needs to integrate actions for the administration of the solid residues. A well as, this City needs to act before the inefficiency of the public politics and to implement the Environmental Education as fundamental element in the learning of the ecocitizenship, with the inhabitants' participation and visitors.